A molecular dynamics study on the thermal conductivities of single- and multi-layer two-dimensional borophene. Issue 1 (25th January 2019) - Liang, Ting; Zhang, Ping; Yuan, Peng; Zhai, Siping; Yang, Daoguo
Abstract: Borophene, a new two-dimensional (2D) structure of boron atoms, has aroused a great deal of attention and research recently. However, research on the thermal conductivity of borophene is still scarce, although this is critical for the potential application of borophene. Accordingly, we investigate the in-plane and cross-plane thermal conductivities of single- and multi-layer borophene using the non-equilibrium molecular dynamics simulations. The effect on the thermal conductivity with respect to sample length, temperature, layer number and mechanical strain is systematically examined. It is found that the in-plane thermal conductivity of infinite-size single-layer borophene exhibits strong anisotropy, which is calculated to be 102.5 ± 1.9 (along the zigzag direction) and 233.3 ± 2.1 W m −1 K −1 (along the armchair direction). Notably, we found that both the in-plane and cross-plane thermal conductivities of borophene are affected by temperature variations, which is the same as other 2D materials. Surprisingly, the in-plane thermal conductivity of multi-layer borophene is insensitive to the layer number. This is attributed to the out-of-plane flexural phonons mode vibration being maintained by the intrinsic bi-layer structure (buckled structure), resulting in a negligible effect of interlayer vdW interactions of the multi-layer structure on the out-of-plane flexural phonons mode. In particular, the cross-plane strain was found to be effective in modulating the cross-plane thermal conductivity of multi-layer borophene in our research. Our findings here are of significance for understanding the thermal transport behavior of single- and multi-layer borophene and promoting their future applications in thermal management and nanodevices.